2013
DOI: 10.1021/am301844c
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing the Interface in Silk–Polypyrrole Composites through Chemical Modification of Silk Fibroin

Abstract: To produce conductive, biocompatible, and mechanically robust materials for use in bioelectrical applications, we have developed a new strategy to selectively incorporate poly(pyrrole) (Ppy) into constructs made from silk fibroin. Here, we demonstrate that covalent attachment of negatively charged, hydrophilic sulfonic acid groups to the silk protein can selectively promote pyrrole absorption and polymerization within the modified films to form a conductive, interpenetrating network of Ppy and silk that is inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
115
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 70 publications
(126 citation statements)
references
References 58 publications
11
115
0
Order By: Relevance
“…CPs are classified as "smart materials" because of their inherent abilitiy to accept ac ounter ion for chargeb alancew hen oxidized and to expel the counter ion when reduced.H owever, CPs suffer from a number of disadvantages:t hey are intractable, insoluble,a nd not thermoformable.T herefore,t heir processability is ac hallenge and restrictst heir direct usage in real-life applications flexibility is ar equirement. Alternatively,C Ps can be made flexible by grafting them on paper, [8] fabric, [9] or by modifying carbon electrodes such as graphene. [10] However, grafted polymers suffer from poor adherence to the surface of their host materials and inhomogeneity leading to non-uniform active surfaces.T herefore,s upercapacitors based on CPs face problems such as capacitance fade,incomplete electrode wetting, restrictions in the thickness of electrodes,m echanical stability, and usage of environmentally toxic chemicals.O n the other hand, metallic semiconducting free-standing flexible films are experimentally challenging and expensive to prepare on alarge scale.…”
Section: Introductionmentioning
confidence: 99%
“…CPs are classified as "smart materials" because of their inherent abilitiy to accept ac ounter ion for chargeb alancew hen oxidized and to expel the counter ion when reduced.H owever, CPs suffer from a number of disadvantages:t hey are intractable, insoluble,a nd not thermoformable.T herefore,t heir processability is ac hallenge and restrictst heir direct usage in real-life applications flexibility is ar equirement. Alternatively,C Ps can be made flexible by grafting them on paper, [8] fabric, [9] or by modifying carbon electrodes such as graphene. [10] However, grafted polymers suffer from poor adherence to the surface of their host materials and inhomogeneity leading to non-uniform active surfaces.T herefore,s upercapacitors based on CPs face problems such as capacitance fade,incomplete electrode wetting, restrictions in the thickness of electrodes,m echanical stability, and usage of environmentally toxic chemicals.O n the other hand, metallic semiconducting free-standing flexible films are experimentally challenging and expensive to prepare on alarge scale.…”
Section: Introductionmentioning
confidence: 99%
“…After 10 days, SF-PPy film lost 65% of its original weight, much higher than that (8%) previously reported for PPy coating on both side of silk substrate. [21] The role of degradation obtained can be attributed to the low β-sheet content in SF obtained via water annealing treatment and the unique bilayer structure of SF-PPy film, which facilitated the enzyme to attack the silk film with cleavage sites available on the surface. After 13 days incubation, SF-PPy film could not keep its original form and crumbled into small fractions due to the degradation of silk substrate.…”
Section: Enzymatic Degradation Of Sf-ppy Filmmentioning
confidence: 99%
“…[20] A degradation profile of 8% mass loss after 10 days incubation in protease XIV solution (10 U mL -1 ) was reported. [21] Towards paving the way for a biocompatible and biodegradable battery, here we report a SFPPy film as an air cathode material in a Mg-air bio-battery. In this SF-PPy film the PPy layer was chemically coated onto one side of a silk film substrate.…”
Section: Introductionmentioning
confidence: 99%
“…Remero et al (2013) demonstrated that covalent attachment of negatively charged, hydrophilic sulfonic acid groups to silk protein can promote pyrrole absorption and polymerization to form conductive, interpenetrating networks of pyrrole and silk that did not delaminate. A variety of small molecule sulfonic acid dopants were utilized to further increase the conductivity and long-term stability of the Ppy network [230] . An engineered recombinant spider silk protein eADF4(C 16 ) was modified with the integrin recognition sequence arginine-glycine-aspartic acid (RGD) by genetic (fusing the genetic sequence encoding GRGDSPG) and chemical (using the cyclic peptide c(RGDfK)) approaches [231] .…”
Section: Physical and Chemical Modificationsmentioning
confidence: 99%